The phenomenon of mobbing in Serbia and Europe - Trišić Marko; Petrović Jovana; Garabinović Dušan (Trendovi u Poslovanju)
As the phenomenon of abuse in the workplace came to a closer public eye of a broader audience through media coverage, there is not a more fertile ground for a fully detailed problem explanation and search for its short or long-term solution. The dose of seriousness concerning the issue of mobbing isn’t only given for its negative effect on a business organization, but also for the mutation of a society’s culture, as well. The research paper outlines the mobbing phenomenon by presenting the theoretical and practical (statistical) diagnosis through which, for a better understanding of the situation, there are added testimonies of mobbing victims, as well as legal and extra-judicial solutions for the issue. The observation of the phenomena is focused on the research and data presentation, using examples from Serbia and Europe. Putting aside the obvious differences in approach, a great space for implementation of European developed countries’ principles can be seen. The same principles could be introduced on the domestic scene, with the introduction of mandatory work conditions that are considered decent.